Novel Use of Scanning Methods to Investigate the Performance of Screw Connections in Timber-Concrete Composite Structures - Mohd Amirul B. Mohd Snin; Moustafa Moufid Kassem (Advances in Civil Engineering)
This paper investigates the shear force capacity, stiffness, and effective length of the connection screws in timber-concrete composite structures. Ten samples (six hardwood and four softwood) were fabricated with the connection screws installed at different angles through the interface. The shear force capacities and the global stiffness characteristics of the connections were determined directly from double shear tests. The local characteristics of the screw connections were investigated by scanning the final residual screw shapes at the end of the tests for softwood specimens. Using the 2D digital scans of the screws, the screw curvatures were determined. From the curvatures, the local distribution of moment along the screw embedded within the concrete at the conclusion of the test was estimated. The distance of the plastic hinge in the screw within the concrete from the interface between the concrete and timber (the effective length) was obtained from the maximum bending moment location calculated via this image scanning method. Empirical equations of effective screw length were developed from the test data and applied in a shear force capacity model for softwood. These new equations of effective length of inclined screws in connections predicted the shear force capacity of the connection better on the softwood specimens. In hardwood specimens, the screw failed in snapping. An equation of shear force capacity was developed based on the influence of the inclination angle of the screw with the reduction factors and can predict the shear capacity of the connection in hardwood specimens.